"Hy wat is en wat was en wat kom": Die God van betrokkenheid volgens Openbaring - Du Rand, Jan A. (Verbum et ecclesia, 2000)
The one who is and who was and who is to come: The God of commitment according to the book of Revelation The theocentricity of Revelation makes an imperative of the placement of the committed One who is and who was and who is to come in the centre of history of mankind. God's character, as depicted in Revelation, is developed through interaction with all creation. The response of nondivine characters to their creator shapes the hearer's/readers' perception of God, who is both revealed and shrouded in mystery through the apocalyptic visions. Through direct, indirect and interdividual characterisation, the focus falls on the expression "who is to come" to emphasise God's commitment, through the sacrifice of the Lamb.